Economics of inequality - Atkinson, A.B. (Oxford, 1983)
This book is about the distribution of income and wealth. It attempts to do three main things. The first is to investigate the evidence about the extent of differences in earnings, other income, and the ownership of capital. What is the share of the top one per cent? How many people are living in poverty? To answer such questions it discusses in depth the conceptual problems and the short-comings of the available evidence. The second aim is to see how the differences can be explained. Why is it that airline pilots earn more than train drivers? Do the differentials reflect training or skill? Do they result from trade union power? Is the market segmented? At the heart of the book are several chapters exploring theories of earnings both old and new and the determinants of the distribution of wealth. At each stage, the relevant empirical evidence is described and assessed. The third objective is to discuss the effectiveness of redistributive policy. What has been the impact of wealth taxes? How effective is the social security system? What reforms of the tax and benefit system could be considered? These questions are of wide and enduring concern, whatever the current priorities of government. Although the book refers particularly to the UK and USA, it has a much wider relevance and will be of interest to readers in many countries.
Keywords: Income distribution